Atlantis and the end of the World - Sergent, Bernard (ARYS. Antigüedad: Religiones y Sociedades, 2019)
The Atlantis´ Disaster, whose author was Plato, falls according to him in the series of other cataclysms of Greek mythology. More globally, it is part of the events that occur on the occasion of changes in the direction of the Universe, which was defined only by him too; he includes the Hesiodic myth of the succession of races.